2019
DOI: 10.5093/jwop2019a1
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Relationship between Unemployment in Young Graduates and Psychological Resources? An Empirical Research from the Conservation of Resources Theory

Abstract: As a consequence of the economic recession initiated in 2007 in the United States and Europe, a great number of people have been left unemployed and, among these, the younger sector of the population had to face more difficulties in accessing the labor market (Wanberg, 2012). One of the European countries most affected by unemployment is Spain. Regarding the data from the Centre for Sociological Research in July 2018 (www.cis.es), unemployment is the main existing problem for 64.3% of the Spanish population, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Meta-analytic evidence also suggests that core self-evaluations such as self-esteem and self-efficacy are associated with mental health outcomes and life satisfaction during unemployment [55]. For instance, young adults who can conserve a sense of environmental mastery, i.e., a sense of being able to influence or impact their environment, show lower levels of psychological distress during unemployment [33], and this is consistent with findings in unemployed adults [56].…”
Section: External and Internal Resources Mitigating The Effects Of Stsupporting
confidence: 64%
See 1 more Smart Citation
“…Meta-analytic evidence also suggests that core self-evaluations such as self-esteem and self-efficacy are associated with mental health outcomes and life satisfaction during unemployment [55]. For instance, young adults who can conserve a sense of environmental mastery, i.e., a sense of being able to influence or impact their environment, show lower levels of psychological distress during unemployment [33], and this is consistent with findings in unemployed adults [56].…”
Section: External and Internal Resources Mitigating The Effects Of Stsupporting
confidence: 64%
“…In line with the SDR model, adaptation to unemployment and individual stress levels may particularly depend on how much internal and external resources are affected by change in employment status. This line of conceptualization has evident parallels with Hobfoll's Conservation of Resources Theory [32], which has also previously been used to conceive adaptation to unemployment in young adults [33].…”
Section: Stress As An Imbalance Of Demands and Resourcesmentioning
confidence: 92%
“…Wanberg (2012), for instance, found that job search clarity had a crucial influence on subsequent job search behaviors and outcomes, given the need for job seekers to develop and implement effective job search strategies (Koen et al, 2010) and maintain strong job search intensity (Manroop & Richardson, 2016; Zikic & Saks, 2009). Finally, we focused on psychological well‐being, given the strong negative implications job loss has on well‐being (Ferreira et al, 2015; McKee‐Ryan et al, 2005; Merino et al, 2019; Paul & Moser, 2009; Vinokur & Caplan, 1987; Wiener et al, 1999).…”
Section: Resiliency and Reemployment Successmentioning
confidence: 99%
“…Autonomy, meaning self-governance and responsible self-control, is the dimension with the strongest effect on psychological well-being in this group ( Fotiadis et al, 2019 ). Furthermore, young people who have found jobs matching their skill sets score higher in the areas of resilience, optimism, autonomy, environmental mastery, self-efficacy, and overall life satisfaction, with fewer indicators of anxiety than are shown by their employment-pathway counterparts who are still seeking jobs ( Merino et al, 2019 ). These findings emphasize the need to train these individuals in how to develop and strengthen the resources that will contribute to their psychological well-being, and which are largely linked to the development of emotional intelligence ( Di Fabio and Kenny, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings emphasize the need to train these individuals in how to develop and strengthen the resources that will contribute to their psychological well-being, and which are largely linked to the development of emotional intelligence ( Di Fabio and Kenny, 2016 ). Specific training in the acquisition of concrete job-finding skills may be especially valuable since it has a positive influence on young peoples’ understanding of how to handle themselves in the workplace ( Guichard et al, 2012 ; Maree and Twigge, 2016 ; Zacher and Schmitt, 2016 ; Merino et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%